The impact of out-of-pocket costs on treatment commencement and adherence in chronic kidney disease: a systematic review. Issue 9 (21st September 2018) - Dodd, Rebecca; Palagyi, Anna; Guild, Laura; Jha, Vivekanand; Jan, Stephen
Abstract: Chronic kidney disease (CKD) is a significant and growing driver of the global non-communicable diseases (NCD) burden, responsible for 1.2 million deaths in 2016. While previous research has estimated the out-of-pocket costs of CKD treatment and resulting levels of catastrophic health expenditures, less is known about the impact of such costs on access to, and maintenance of, care. Our study seeks to fill this gap by synthesizing available evidence on cost as a determinant of CKD treatment discontinuation. We searched for studies which considered the financial burden of treatment and medication for CKD patients and the extent to which this burden was associated with patients forgoing or discontinuing treatment. We identified 14 relevant studies, 5 from high-income countries and 9 from low-middle income countries. All suggest that cost adversely influences adherence to CKD medication and dialysis treatment. In poorer countries, those entering treatment programs were typically diagnosed late, under-dialysed and suffered very high levels of mortality. Identified studies present consistent findings regardless of study context: cost is barrier to treatment and a driver of non-adherence and discontinuation, with poorer households worst affected. This is in line with previous research. Major gaps in the literature remain, however, in relation to differential impact of the cost burden on men and women, the coping strategies of poor households and the effect of insurance coverage.